Control by Lyapunov functions for Robot Scorbot ER 5 Plus - Álvarez Sánchez, Pedro Harvey (I+ T+ C- Research, Technology and Science, 2015)
This paper present has as objective the generation of a tool for the analysis of robot manipulator controllers, such as PID and CTC Lineal Controllers, compared to the non-lineal, more precisely, the Trajectory Adaptive Controller, to achieve it, the Robot Scorbot- ER 5plus has been used since it has a great popularity in the academic and industrial fields. An identification and modeling of its Geometrical models, as well as dynamical and kinematical has been made. Also, a comparison of the results of the controllers regarding the development of trajectories in the operational and articular space, including the errors in the signal that often occur in these kind of systems due to mistakes in modeling and external disturbance.